EXPLORING SISTEM MARKETING ONLINE DAN OFFLINE DI WABISABI COSMETICS PROGRAM MBKM MAHASISWA INDO GLOBAL MANDIRI - Callistasari, Nidia Putri; Hertati, Lesi; Asharie, Asmawati (JOURNAL OF SUSTAINABLE COMMUNITY SERVICE, 2022)
Wabisabi, a store that offers a wide array of cosmetics and beauty products from leading Indonesian and international brands, is capitalizing on the momentum of rapid growth in the face and body care industry. Along with the evolution of the times and the increased understanding of women and men towards skincare needs, Wabisabi found substantial opportunities in marketing its products. With consumers increasingly open to the concept of face and body care, Wabisabi is expanding its target market, not only to women, but also to men who are increasingly concerned about their self-care. In the face of ever-changing market dynamics, Wabisabi realizes that the right marketing strategy is essential to maximize sales potential. Positive developments in people's views towards facial care products across different age groups create a solid foundation for Wabisabi's business growth. Hence, the need to implement a holistic marketing system to explore this huge opportunity. A comprehensive approach involves offline sales strategies through physical stores as well as online market penetration through social media platforms that are currently highly influential in influencing consumer behavior. The utilization of social media as a key marketing channel proves its effectiveness, given the immense influence it has on people across segments. However, awareness of the potential of offline sales also remains relevant, given that some consumers still prefer to shop in person and try products in person before deciding on a purchase.